Design of Microstrip Patch Antenna using for Wireless System - Kaur, Ravinder; *, Ruchi (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
This paper presents the design and simulation results of a design to microstrip patch antenna using with two feeding techniques for Wireless (1.9 GHz) applications. The proposed antenna is designed on FR4 substrate with a thickness of 1.6 mm, permittivity of 4.4 and tangential loss of 0.025. The size of the antenna is 37.26 × 48 ×1.6 mm3 and has a Microstrip feed line and Inset feed line. The antenna has a low return loss and VSWR. Our aim to improve the return loss and VSWR using MATLAB and CST Microstrip Studio software and comparison of the MATLAB and CST Microstrip Studio software.